Pembelajaran Iqra dengan metode individual dalam perspektif cara belajar siswa aktif pada anak usia dini - Niswatus Zahra; Aulia Eka Prasanti; Dewi Yunjiati; Sagita Faidatun Nikmah; Sutrimo Purnomo (Liberi, 2026)
This study aims to examine the implementation of Iqra learning using the individual method from the perspective of Active Student Learning (CBSA) in early childhood education at RA Masyithoh 13 Sokaraja Lor. This topic is significant as learning to read the Qur’an at an early age not only focuses on reading skills but also emphasizes students’ active participation and learning independence. The research employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The findings indicate that Iqra learning is conducted regularly using an individual approach, where children read in turns according to their respective abilities. The teacher primarily acts as a listener and provides indirect cues to correct mistakes, encouraging children to be more active and self-reliant. The application of CBSA principles is evident during individual reading activities; however, it is less optimal when children are waiting for their turns. The individual method is effective in improving reading accuracy and fostering independence, although it presents challenges in time management and maintaining the engagement of all students. Therefore, CBSA-based Iqra learning needs to be further developed through more varied strategies to create a more comprehensive and meaningful learning experience for early childhood learners.